Foliar biofortification with iron improves nutraceutical quality and antioxidant capacity in lettuce - Preciado-Rangel, Pablo; Valenzuela-García , Ana Alejandra; Pérez-García, Laura Andrea; González-Salas , Uriel; Ortiz-Díaz, Sergio Arturo; Buendía-García, Alain; Rueda-Puente, Edgar Omar (REVISTA TERRA LATINOAMERICANA, 2022)
Iron (Fe) is an essential trace element for human health and its deficiency affects 1.2 billion people in the world. Agronomic biofortification can mitigate this deficiency as its application in crops improves the biosynthesis of bioactive compounds and promotes their bioaccumulation. Our research aims to evaluate the effect of the foliar application of Fe (FeSO4) on the yield, biosynthesis of bioactive compounds and accumulation in lettuce. For this, five treatments were applied by foliar route: 0, 10, 20, 30 and 35 µM L‑1. At harvest, the nutraceutical quality and the accumulation of Fe in leaves were quantified, as well as the productivity of the lettuce plant. Biofortification with Fe positively modified the biosynthesis of phytochemical compounds and their concentration in lettuce leaves, without affecting the yield. Fe foliar spraying is an alternative to increase the biosynthesis of phytochemical compounds and increase the concentration of this element in lettuce.